2018
DOI: 10.1002/adfm.201705463
|View full text |Cite
|
Sign up to set email alerts
|

Space‐Charge‐Stabilized Ferroelectric Polarization in Self‐Oriented Croconic Acid Films

Abstract: Great progress has been made recently in molecular ferroelectrics with properties even comparable to those of inorganic ferroelectrics. However, it is difficult to develop basic thin films and devices for practical applications since most molecular ferroelectrics are uniaxial. The single polar axes of crystallites inside their films, if available, are usually oriented randomly. These can induce the components without contribution to ferroelectric polarization and a large depolarization electric field to suppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…In 2018, to prove that ferroelectric polarization can also achieve interface memory switching in uniaxial molecular ferroelectric materials, Hu et al used croconic acid crystallites to fabricate thin films for capacitive devices. [249] It can be found that the device exhibits an obvious ferro-polarized non-volatile memory switching behavior (Figure 30i,j). The hysteresis loops are unclamped at a voltage of 0 V, and the hysteresis loops of the first and third quadrants are mostly clockwise, which is a typical [246] Copyright 2019, Wiley-VCH.…”
Section: Organic Nonvolatile Ferroelectric Transistor Memoriesmentioning
confidence: 95%
“…In 2018, to prove that ferroelectric polarization can also achieve interface memory switching in uniaxial molecular ferroelectric materials, Hu et al used croconic acid crystallites to fabricate thin films for capacitive devices. [249] It can be found that the device exhibits an obvious ferro-polarized non-volatile memory switching behavior (Figure 30i,j). The hysteresis loops are unclamped at a voltage of 0 V, and the hysteresis loops of the first and third quadrants are mostly clockwise, which is a typical [246] Copyright 2019, Wiley-VCH.…”
Section: Organic Nonvolatile Ferroelectric Transistor Memoriesmentioning
confidence: 95%
“…Likewise, Yuan et al 126 studied the temperature dependence of the nucleation rate of CA films with and without electric field-assisted growth and observed that the maxima of the grain density shifts in temperature when an electric field is applied during growth. Similarly, the void defects arising at the interface between CA films and substrates such as Si and SiO 2 have been studied by Peterson et al 127 Furthermore, Hu et al 70 have been able to grow micrometer thick CA films with crystallites uniaxially oriented, c -axes perpendicular to the film plane, without using any in situ electric field and have demonstrated stable ferroelectric properties as well as a non-volatile memory switching behavior stabilized by space charges.…”
Section: Croconic Acidmentioning
confidence: 99%
“…Following the discovery of ferroelectricity in the crystal form of CA, several groups have started working on various aspects of the powder, [48][49][50] bulk single crystal, [51][52][53][54][55][56][57][58][59] self-assembled co-crystal, 60,61 composite film 62 and thin film [63][64][65][66][67][68][69][70] forms of the molecule. Most of the studies have focused on the ferroelectric and optical properties of the macroscopic crystals of CA.…”
Section: Introductionmentioning
confidence: 99%
“…Limited by the uniaxial nature, the P s value of croconic acid thin films is only about 0.4 mC cm À2 , which is one-fiftieth of a single crystal sample. 36,37 In addition, the mechanical strength, hygroscopicity, and solubility are also obstacles to the practical application of molecular ferroelectrics. Therefore, finding proper protocols for achieving highly oriented ferroelectric films has become the hot issue in molecular ferroelectric chemistry.…”
Section: Introductionmentioning
confidence: 99%